(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The GNV Learning Center, acting as the community engagement partner, had difficulties enhancing the participants’ competences within the context of implementing Internal Control Over Financial Reporting (ICOFR). Additionally, a significant number of trainees came from businesses that did not have sufficient documentation of their internal controls and had minimal experience recognizing risks or evaluating their effectiveness. In order to address these deficiencies, a community service program with the name "Mastering ICOFR: Building Effective Internal Control Systems for Compliance and Financial Reporting Accuracy" was developed. The program’s objective is to enhance both the theoretical grasp of the COSO framework and the practical skills associated with it. The program was presented in a variety of formats, including interactive seminars, group exercises, discussions based on real-world scenarios, and simulations of internal audits. Additionally, participants were provided with access to digital modules and online mentoring support for a period of three months, in addition to the in-person training that lasted for two days. The evaluation, which consisted of pre- and post-tests, revealed that the participants’ abilities had improved by an average of 33 percent. A number of significant learning outcomes were the enhancement of risk mapping, the recording of internal controls, and the capability to identify gaps in the system. This program was successful in contributing to the development of a culture that prioritizes compliance, accountability, and transparency within the organizations that made up the participants. We recommend replicating the program model in other industries facing comparable governance difficulties due to its adaptability.